Cardiorespiratory Fitness Cut-Points Are Related to Body Adiposity Parameters in Latin American Adolescents - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Background and Objectives: A deficiency exists in the criterion-referenced cut-points for field-based cardiorespiratory fitness (CRF) in Latin American youths. The aims of the present study were two-fold: (1) To identify the ability of CRF estimated by the 20-m shuttle-run test (20mSRT) to differentiate between “healthy” and “unhealthy” phenotypes (by adiposity) in adolescents; (2) to assess the association between obesity and relative peak oxygen uptake (VO2peak) in a large and diverse sample of Latin American youths. In total, 72,505 adolescents aged between 13 and 15 years were recruited from Chile and Colombia (47.5% girls). Materials and Methods: The waist circumference (WC) and waist-to-height ratio (WHtR) were used to identify body adiposity markers. CRF was measured using the 20mSRT (VO2peak). Receiver operating characteristic curves and logistic regression were used to determine the discriminatory ability of CRF to predict body adiposity parameters. Results: For boys and girls, VO2peak showed a significant predictive capacity to detect body fat (area under the curve [AUC] > 0.62). The sensitivity of VO2peak was medium (>63%) for all age- and sex-specific cut-points, with optimal cut-points in 13- to 15-year olds for obesity identified as 43.77 mL·kg-1·min-1 and 38.53 mL·kg-1·min-1 in boys and girls, respectively. Conclusions: According to these cut-points, adolescents with low CRF were more likely to be obese either by WC or WHtR. The CRF cut-points can be used as quantitative markers for a healthier body in Latin American adolescents. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.